1988
DOI: 10.1002/hep.1840080506
|View full text |Cite
|
Sign up to set email alerts
|

Cellular interactions promote tissue-specific function, biomatrix deposition and junctional communication of primary cultured hepatocytes

Abstract: Hepatocytes, prepared from normal adult rat liver, were seeded onto a collagen substratum and cultured alone or in the presence of rat liver endothelial cells. When hepatocytes were cultured alone in a hormonally defined serum-free medium, decreased albumin production and rapid morphological deterioration of bile canaliculi structures and gap junctions occurred within 4 to 5 days. In contrast, hepatocytes cocultured with liver mesenchymal cells remained morphologically intact and biochemically functional for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
76
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(78 citation statements)
references
References 37 publications
2
76
0
Order By: Relevance
“…The enhanced survival and function of hepatocytes cocultured with rat liver epithelial cells have been confirmed by many investigators (134,(138)(139)(140)(141)(142)(143); the induction of CYP2B1 and CYP2B2 by phenobarbital has also been demonstrated (137,144). Moreover, other cells have been effective, including both liver endothelial cells and nonhepatic cells (145)(146)(147). Studies from our laboratory (148,149) have shown that the presence of an integral plasma membrane glycoprotein is a prerequisite to obtain longterm survival of differentiated hepatocytes in coculture.…”
Section: However Survival and Metabolic Compe-mentioning
confidence: 75%
“…The enhanced survival and function of hepatocytes cocultured with rat liver epithelial cells have been confirmed by many investigators (134,(138)(139)(140)(141)(142)(143); the induction of CYP2B1 and CYP2B2 by phenobarbital has also been demonstrated (137,144). Moreover, other cells have been effective, including both liver endothelial cells and nonhepatic cells (145)(146)(147). Studies from our laboratory (148,149) have shown that the presence of an integral plasma membrane glycoprotein is a prerequisite to obtain longterm survival of differentiated hepatocytes in coculture.…”
Section: However Survival and Metabolic Compe-mentioning
confidence: 75%
“…8. Hepatocytes cultured in a collagen double-gel have been shown to exhibit native cell-cell contacts such as E-cadherin and bile canaliculi, 34 but do not express sinusoidal receptors such as EGF-R 34 and LDL-R. Hepatocytes cocultured with 3T3 fibroblasts exhibit hepatic cell-cell contacts such as connexin-32 44 and bile canaliculi, 24 but also do not express the EGF-R and LDL-R. On the other hand, hepatocytes cocultured with LSEC show both traditional polarity markers, 45,46 and express a high level of sinusoidal receptors (EGF-R, LDL-R) at the interface between the hepatocytes and the LSEC. At least part of the interaction between hepatocytes and LSECs has been shown to be mediated by growth factors.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21] In the liver sinusoid, LSECs and hepatocytes are arranged in layers with the intervening space occupied by the extracellular matrix (ECM) of the perisinusoidal space (space of Disse); collagen I is one of the major components in this matrix. [22][23][24][25] While hepatocytes are primarily responsible for various secretion and metabolic functions of the liver; LSECs line the sinusoids, isolating hepatocytes from the sinusoid flow and are first to be exposed to various toxic and benign factors circulating through the hepatic sinusoids.…”
mentioning
confidence: 99%